A study on nutritional status, mealtime behavior and food refusal among Autism Spectrum Disorder (ASD) and Typically Developing (TD) children aged 3 to 11 years old in USM Kubang Kerian, Kelantan - Hashim, 'Isyatin Munirah (Pusat Pengajian Sains Kesihatan, 2017)
A cross-sectional study was conducted to investigate the nutritional status, mealtime behaviors and food refusal among Autism Spectrum Disorder and Typically Developing children aged 3 to11 years old in Universiti Sains Malaysia Kubang Kerian, Kelantan (97 children). In this study, nutritional status was calculated and categorized based on CDC (2000). On the other hand, mealtime behaviors was determined using Brief Assessment of Mealtime Behavior in Children (BAMBIC). BAMBIC questionnaires consisted 3 factors which were Food Refusal, Disruptive Behaviors and Limited Variety. While food refusal among respondents was determined by using Food Preferences Inventory (FPI) based on 12 group which namely cereals and cereal products, meat and meat products, fish and seafood, eggs, legumes and legume products, milk and dairy products, vegetables, fruit, confectionery, beverages, spreads, seasonings and flavoring. Result showed that ASD children possessed higher in both underweight, overweight and obese as compared to TD children. In mealtime behaviors outcome, the food refusal and disruptive behavior factor were significantly different among ASD children compared to TD children. However, for limited variety factor, not significant mean differences was noted between ASD and TD children. The common food refusal that significantly different among ASD and TD children were cereal and cereal product (p <0.001), meat and product (p=0.039), bread spread (p=0.017) and confectionery cake (p=0.012). However, ASD and TD children do not show significant mean differences in refusing vegetables (p=0.239), fruits (p=0.089), fish and seafood (p=0.090), beverages (p=0.456)), milk and milk product (p=0.387) and flavoring and seasonings (p=0.925). In conclusion, children with ASD more likely to suffer underweight, overweight and obese issues as compared to TD children. This might be related to higher unhealthy food intake and less vegetables and fruits intake so leads some of them to overweight and obese. However, there were also a few of them might consuming less energy dense food and had higher mealtime behaviors problem so leads them to have lower BMI compared to TD children.